Deciphering Celebrity Worship Phenomenon: Simulation and Analysis using SFR Mathematical Model among Fans in South Sulawesi - Minggi, Ilham; Side, Syafruddin; Yusuf S.A.P., Andi Muh. Ridho; Arsita, Asriani (Universitas Cokroaminoto Palopo, 2024)
This study delves into the mathematical SFR model capturing the pace of Celebrity Worship Behavior among devoted K-Pop enthusiasts. Primary data is harnessed via questionnaires directly sourced from the community within South Sulawesi Province, offering insights into the rhythm of Celebrity Worship Behavior among K-Pop aficionados. The research embarks on constructing the SFR model and subsequently navigating through an array of analyses and simulations pertaining to Celebrity Worship Behavior in the K-Pop sphere. This comprehensive approach encompasses pinpointing equilibrium junctures, scrutinizing model stability, computing the fundamental reproduction number (R0), orchestrating model simulations using Maple software, and untangling the implications of simulation outcomes. Within this article, the SFR mathematical model materializes through a synthesis of analysis and simulation, uncovering two equilibrium points: the unconstrained equilibrium of Celebrity Worship Behavior in the realm of K-Pop enthusiasts, and the equilibrium specific to this distinctive behavior. A calculated basic reproduction number of R0=0,425 alludes to a decline in the populace engaging in Celebrity Worship Behavior within the K-Pop community.